Persuasive technologies and the right to mental liberty: the ‘smart’ rehabilitation of criminal offenders - Ligthart, S; Meynen, G; Douglas, T (Cambridge University Press, 2022)
Conventional medical ethics, medical law and human rights protect us against the technological manipulation of our bodies, in part through recognising and enforcing a right to bodily integrity. In this chapter, we will explore the possibility of that we might also protect ourselves against the technological manipulation of our minds through recognising an analogous right to mental integrity. In the first part of the chapter, we describe some of the recent developments in the areas of persuasive and monitoring technologies, and how they are currently being used, e.g., in criminal justice and on the internet. In the second part we survey existing and proposed novel human rights law relevant to mental integrity. In the third part we argue that, though the right to mental integrity has thus far particularly been debated regarding neurointerventions, it would also apply to at least some persuasive and monitoring technologies. Finally, fourth, we consider how existing (i) law and (ii) philosophical scholarship might help to resolve the thorny question of which persuasive and monitoring technologies would infringe the right to mental integrity.